Pengaruh Tren Workation Terhadap Produktivitas Kerja Dengan Work Life Balance, Memorable Tourism Experience dan Adaptabilitas Teknologi Sebagai Variabel Intervening Pada Generasi Milenial - Angela, Patricia Naomi; Rahmanita, Myrza; Ingkadijaya, Rahmat (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the impact of workation on the work productivity of millennials in Indonesia, taking into account the mediating roles of work-life balance, memorable tourism experience, and technological adaptability. The research employs a descriptive quantitative approach, with the population consisting of millennial workers who participated in workation programs in Bali, Yogyakarta, and Bandung during the 2020–2023 period. A total of 300 respondents were determined using probability sampling with the Slovin formula at a 5% margin of error and were then proportionally distributed across the three regions. Data were collected through primary surveys (questionnaires) and secondary sources (literature review), and analyzed using descriptive statistics and Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that all hypotheses were supported, with key findings showing that technological adaptability, memorable tourism experiences, and work-life balance have a positive and significant effect on work productivity. Workation also directly influences these three variables as well as productivity itself. Furthermore, there is a significant indirect effect, where workation boosts productivity through the mediating paths of balanced life, meaningful travel experiences, and tech adaptability. These findings affirm that workation is an effective flexible work strategy for enhancing employee performance through adaptive, balanced, and inspiring work environments. The study also has significant implications for the development of the tourism sector and labor policy in the digital era.